2001
DOI: 10.1002/app.1820
|View full text |Cite
|
Sign up to set email alerts
|

Cationized sawdust as ion exchanger for anionic residual dyes

Abstract: Using the same procedure as recently described for cotton fiber, the preparation of cationized wood sawdust was performed by treating alkali sawdust with epoxy propyl trimethyl ammonium chloride (EPTMAC) in a nonaqueous medium (dimethylformamide, DMF). The fixation of ammonium groups onto sawdust was monitored by weight uptake, nitrogen content determination, and infrared spectroscopy. EPT-MAC-sawdust with a 0.5 wt % nitrogen content is then used as adsorbent for acid dyes (Acid Blue 25, Acid Yellow 99, Reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 25 publications
4
39
1
Order By: Relevance
“…In contrast, however, internal cationic sites (and, in particular, those occurring in the bulk of the amorphous zones of the cellulosic sorbent) cannot adsorb the same number of surfactant molecules due to the size of the resulting hemi-micelle. A similar observation was made previously with respect to dye molecules adsorbed on the same cationized sorbents (Baouab et al 2000(Baouab et al , 2001: the large dye molecules were incapable of saturating all the cationic sites anchored on to the sorbent. As a consequence, the surface cationic sites must involve hemi-micelles with a higher number of surfactant molecules, so that the reported value of 4.5 for SDS onto polystyrene (Zhu et al 1989) would also appear reasonable in the present case.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…In contrast, however, internal cationic sites (and, in particular, those occurring in the bulk of the amorphous zones of the cellulosic sorbent) cannot adsorb the same number of surfactant molecules due to the size of the resulting hemi-micelle. A similar observation was made previously with respect to dye molecules adsorbed on the same cationized sorbents (Baouab et al 2000(Baouab et al , 2001: the large dye molecules were incapable of saturating all the cationic sites anchored on to the sorbent. As a consequence, the surface cationic sites must involve hemi-micelles with a higher number of surfactant molecules, so that the reported value of 4.5 for SDS onto polystyrene (Zhu et al 1989) would also appear reasonable in the present case.…”
Section: Resultssupporting
confidence: 81%
“…However, with DBS, the value of ca. 1.8 obtained was lower as might be expected from the lower aggregation number, n, for its micelles, with a value of 27 having been reported (Bi et al 2001) compared to 69 for SDS (Shah et al 2001).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Cellulose derivatives have been particularly investigated during the treatment of effluents. [33][34][35] In a previous work, Baouab et al, 7 have chemically modified the cotton fiber by ethylene diamine and then the ethylene diamine-grafted groups immobilizes Cu(II) ions was tested for the adsorption of Calma and AB25 as ligands in the metal-coordinating process. The objectives of this article concern the description, for the first time, of the feasibility and the characterization of a ternary complex formation between the two model ligands (AB25 and Calma), Cu (II) ions, and crosslinked chitosan microspheres using a batch process under several experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…11,26,27 Gruber et al 28 examined new approaches for attaching quaternary ammonium groups to cellulose and demonstrated that the use of oligoionomers results in very high cationic densities on the fiber surfaces.…”
mentioning
confidence: 98%